Safety and immunogenicity of high-dose quadrivalent influenza vaccine in adults ≥65 years of age: A phase 3 randomized clinical trial. Issue 39 (16th September 2019) - Chang, Lee-Jah; Meng, Ya; Janosczyk, Helene; Landolfi, Victoria; Talbot, H. Keipp; ,
Highlights: High-dose trivalent influenza vaccine is licensed for adults ≥65 years of age. A quadrivalent formulation with antigen from both B lineages has been developed. Adding the second B strain improved immunogenicity against the added strain. Immunogenicity against the other strains remained the same. The vaccine's tolerability was unaffected by adding the second B strain. Abstract: Background: A high-dose, split-virion inactivated trivalent influenza vaccine (IIV3-HD; Fluzone® High-Dose, Sanofi Pasteur) is available for adults ≥65 years of age. This study examined the safety and immunogenicity of a quadrivalent high-dose split-virion inactivated influenza vaccine (IIV4-HD). Methods: This was a randomized, modified double-blind, active-controlled, multi-center trial in healthy adults ≥65 years of age. Subjects were randomized in a 4:1:1 ratio to receive a single intramuscular injection of IIV4-HD, the licensed IIV3-HD, or an IIV3-HD containing the alternate B-lineage strain. Hemagglutination inhibition (HAI), seroneutralisation, and anti-neuraminidase antibody titers were measured at baseline and day 28. Solicited reactions were collected for up to 7 days, unsolicited adverse events up to 28 days, and serious adverse events up to 180 days. The primary immunogenicity objective was to demonstrate that IIV4-HD induces HAI geometric mean titers (GMTs) and seroconversion rates that are non-inferior to those induced by IIV3-HD. Secondary objectives were to describe the safety of IIV4-HD and IIV3-HD and to demonstrate that IIV4-HD induces HAI GMTs and seroconversion rates that are superior to those induced by IIV3-HD not containing the same B-lineage strain. Results: The study included 2670 adults ≥65 years of age. For all four strains, HAI GMTs and seroconversion rates induced by IIV4-HD were non-inferior to those induced by IIV3-HDs containing the same strains. For both B strains, HAI GMTs and seroconversion rates induced by IIV4-HD were superior to those induced by IIV3-HD not containing the same B–lineage strain. Seroneutralisation and anti-neuraminidase antibody responses, measured in a subset of subjects, were similar. No new safety concerns were identified, and the safety profiles of IIV4-HD and IIV3-HD were similar. Conclusions: Adding a second B strain in IIV4-HD resulted in improved immunogenicity against the added strain without compromising the immunogenicity of the other strains or the vaccine's tolerability. Clinical trial registration: NCT03282240.